Corruption-Growth Nexus in the Emerging Market Economies: Empirical Evidence Using Panel Data - Rehman, Muhammad Atiq ur; Bashir, Furrukh; Rashid, Muhammad Khalid; Hussain, Altaf (iRASD Journal of Economics, 2023)
Corruption is a governance dilemma in emerging market economies (EMEs) with fragile law enforcement systems. Using annual data from 1997 to 2020, this study explores corruption-growth nexus in the World's most important emerging market economies. Since it takes into account the intrinsic characteristics of each country, the panel data fixed effect estimation method appears to be the best option. The fixed effect estimation results reveal that corruption has a significantly negative impact on economic growth of the EMEs under consideration, after controlling for the government spending, investment, human capital, trade openness, and population. The random effect estimation method used as a fallback does not significantly alter the empirical findings. A noteworthy fact revealed by the pragmatic findings is that when corruption is significant, the effect of government spending on economic growth becomes negative due to embezzlement and misallocation of public coffers.